Analysis Of Quality Improvement Of Two Wheel Motor Vehicle Services Using Quality Function Deployment Method At Rezky Jaya Motor Workshop Makassar - Siswanto; Yan Herdianzah; Nurhayati Rauf; Alim Suja’setyahadi (Journal of Industrial System Engineering and Management, 2022)
ABSTRACT Resky Jaya Motor Makassar is one of the general motorcycle repair shops serving services such as medium service, light service, and heavy service. There are several complaints about service satisfaction at the Resky Jaya Motor workshop, most of the se complaints are in service, work supervision, vehicle systems, and inapropriate processing times. The purpose of this study is to know the service attributes desired by the customer and to know the service attributes that provide satisfaction to the customer. The method used in this research is Quality Function Deployment (QFD), as a method to transform customer desires into appropriate technical requirements at each stage of the life cycle of a product to product concept then sales and service. The results of this study indicate that the service attributes desired by service users based on observations there are 20 statement attributes, and in improving the quality of vehicle service services at the Rezky Jaya Motor Makassar workshop, technical engineering is carried out on the wishes of service users contained in the list of service users' needs so that service attributes which is expected to provide satisfaction to service users